Índices fisiotécnicos, fases de crecimiento y etapas de desarrollo de la planta de arroz - Jarma O., Alfredo; Degiovanni Beltramo, Víctor M.; Montoya, Rafael A. (International Center for Tropical Agriculture, 2010)
Physical-technical indicators, growth phases, and development stages of the rice plant The indexes or indicators most commonly used by researchers to analyze plant growth—an information used by researchers, technicians, and farmers to optimize crop production—are described. These indicators are parameters that help quantify the growth of a plant organ or population, analyze the ability of a plant species to grow in a given environment, compare this ability with that of other species, and explain the performance of a given plant species over time. They can be grouped into physical-technical indicators of growth and development, which include growth curves (for example, sigmoid curves); quantifiable parameters for analysis, which include growth rates (absolute, relative, simple, compound) as well as duration index and total dry matter production; and growth rates. The growth rates most frequently used to study the rice plant and crop are described in detail: absolute growth rate (AGR), relative growth rate (RGR), leaf area ratio (LAR), leaf area index (LAI), net assimilation rate (NAR), and crop growth rate (CGR). The different processes and factors that intervene in dry matter production are also indicated, such as photosynthesis, the carbohydrates produced during photosynthesis (which contribute to grain yield), and the photosynthesis/photosynthate ratio. The growth phases (vegetative, reproductive, and physiological maturity) of the rice plant are described in detail as well as its different development stages, according to the BBCH scale.